The right to speak Irish: représentation de la langue gaélique en tant qu’enjeu de mobilisation militante en Irlande du Nord - Müller, Viviane (My University, 2000)
The Irish language movement in Northern Ireland was formed in the 1970’s. Pragmatic and symbolic implications of this minority language revival considerably evolved, reflecting and depending on important political changes happening in this European province. The following article deals with the representation of Irish language and the most recent strategy developed by the Irish language activists for its promotion. This presentation is relating on data collected in 1997 amongst Irish Medium Education teachers in Belfast, as part of an anthropological study conducted for the University of Neuchâtel (Switzerland).